Remedy for Now but Prohibit for Tomorrow: The Deterrence Effects of Merger Policy Tools - Jo Seldeslachts; Joseph A. Clougherty; Pedro Pita Barros (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
Antitrust policy involves not just the regulation of anti-competitive behavior, but also an important deterrence effect. Neither scholars nor policymakers have fully researched the deterrence effects of merger policy tools, as they have been unable to empirically measure these effects. We consider the ability of different antitrust actions - Prohibitions, Remedies, and Monitorings - to deter firms from engaging in mergers. We employ cross-jurisdiction/pan-time data on merger policy to empirically estimate the impact of antitrust actions on future merger frequencies. We find merger prohibitions to lead to decreased merger notifications in subsequent periods, and remedies to weakly increase future merger notifications: in other words, prohibitions involve a deterrence effect but remedies do not.
urn:nbn:de:bvb:19-epub-13334-4
Keywords: L40; L49; K21; 330